Extraction of Papaya Leaves (Carica papaya L.) Using Ultrasonic Cleaner - Lina Fauziah; Miladiatul Wakidah (EKSAKTA: Journal of Sciences and Data Analysis, 2019)
Extraction of papaya leaves (Carica papaya L.) using Ultrasonic Cleaner has been performed. Papaya leaves were extracted for 6 hours in a methanol as solvent. The results of phytochemical screening showed that methanol extract contained secondary metabolites of flavonoids, alkaloids, tepenoid, saponin, and phenolic classes. Methanol extract was then partitioned liquid-liquid with n-hexane. Quantitative analysis of partitioning of n-hexane using papaya leaves using Gas Chromatography-Mass Spectrometry (GC-MS) showed the presence of neophytadiene (1.59%), palmitic acid (1.35%) and methyl linolenate (3.33%). The results showed that Ultrasonic Cleaner can be used to ultrasonic-assisted extraction of natural products especially for papaya leaves.